PENGARUH INFLASI, KURS DOLAR AS, DAN IJEPA TERHADAP EKSPOR TEKSTIL PAKAIAN JADI INDONESIA KE JEPANG - Rismayanti, Ni Made Dwi; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
Indonesia is an agrarian country that makes the non-oil and gas sector as a mainstay sector in trade in this non-oil and gas sector whose influence in trade is industrial commodities such as those that enter into non-oil and gas exports consist of textile commodities apparel whose main purpose of export is Japan, and to facilitate international trade made international trade agreements one of which is between Indonesia and Japan known as Indonesia-Japan Economic Partnership Agreement (IJEPA). Based on the results of research and analysis can be concluded that simultaneously variable Inflation, EXCHANGE Rate OF US Dollar and IJEPA has a significant effect on the Export Value of Textile Apparel Indonesia. Inflation partially negatively affects the export value of Indonesian Apparel Textiles, while the EXCHANGE Rate of US Dollar and IJEPA has a significant positive effect on The Export of Indonesian Apparel Textiles. Variable Exchange Rate US Dollar has a more dominant influence on the value of Textile Exports Finished Clothing Indonesia than other free variables namely variable Inflation and IJEPA. Keywords :Inflation, US Dollar Exchange Rate, IJEPA, Export Value of Apparel Textiles Klasifikasi JEL: E31, F21, F53, C67